Pervasive, tholeiitic refertilisation and heterogeneous metasomatism in Northern Victoria Land lithospheric mantle (Antarctica) - PELOROSSO, Beatrice; BONADIMAN, Costanza; COLTORTI, Massimo; FACCINI, Barbara; Melchiorre, Massimiliano; Ntaflos, Theodoros; Gregoire, Michel (Lithos, 2016)
The petrology of peridotite xenoliths in the Cenozoic volcanics from Greene Point (Northern Victoria Land, Antarctica) provides newconstraints on the characterisation of the lithospheric mantle beneath theWest Antarctic Rift. Based on mineral major and trace element models, this mantle domain is proposed to represent a residuum after 10% and 20% partial melting. Moreover, melting models and isotopic results for Sr and Nd systematics highlight the substantial contribution of tholeiiticmelts percolating through peridotites. Close correlation with trace element contents in clinopyroxene phenocrysts fromFerrar and Karoo tholeiites allows us to ascribe this refertilisation event to the Jurassic. This asthenospheric meltwas also able to transfer a garnet signature to the Northern Victoria Land mantle segment. The rare presence of glass and secondary phases indicate that Greene Point xenoliths were heterogeneously affected by alkaline metasomatism, probably related to the West Antarctic Rift System opening; this has also been widely observed in other Northern Victoria Land localities (i.e., Baker Rocks). Temperature and fO2 were calculated (950 °C; Δlog fO2 (QFM), −1.70 to −0.39) at a fixed pressure of 15 kbar, confirming the tendency of the anhydrous Greene Point xenolith population to have higher equilibration temperatures and comparable redox conditions, compared to the nearby amphibole-bearing peridotites from Baker Rocks.